Hama Penggerek Buah Kakao - Kendala Utama Industri Kakao Indonesia dan Saran Pengelolaannya - Soekadar Wiryadiputra (Jurnal Perlindungan Tanaman Indonesia, 1996)
Outbreak of cocoa pod borer has occurred inCentral Sulawesiand other Indonesian provinces since 1991. The reason of the outbreak has not been clearly defined, however, it was presumed that the event look place after tremendous expansion of cocoa plantation in the last two decades. Until December, 1995 the pest has infested 11 provinces including several main cocoa producing areas ofIndonesia. Total cocoa area damaged by the pest is about 40,000 ha. Bioecological aspects and management of the pest were reviewed from some recent literatures. These information should be useful to arrange the control strategy of the pest inIndonesia. Control measures developed in other countries can be adopted directly in handling the pest, especially for short term practices.